Teachers' technology use for teaching: Comparing two explanatory mechanisms. (August 2021) - Backfisch, Iris; Scherer, Ronny; Siddiq, Fazilat; Lachner, Andreas; Scheiter, Katharina
Abstract: Although integrating technologies for teaching has received much attention, research demonstrated that teachers rarely use technologies likely because of low levels of technology-related motivation. Theories on teacher motivation such as Expectancy-Value Theory and Technology Acceptance models differ in how they conceive the influence of motivation on technology integration. To investigate these conflicting assumptions, we conducted a survey study within one-to-one technology-enhanced schools with N  = 524 in-service teachers. Findings from structural equation modeling showed that rather than being mutually exclusive, the two perspectives should be integrated to inform research and practitioners about the implication of teacher motivation for technology integration. Highlights: We propose a synergism of two perspectives on teachers' technology use. Technology integration comprises quantitative and qualitative aspects. Direct and indirect relations between motivation and technology use exist. A model integrating a concurrent and cascade mechanism fits the data best. TPACK self-efficacy is critical for successful technology integration.